Optimization of Quality Management in Quality Based Curriculum Development - Sudarma Sudarma; Titi Hendrawati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Evaluation is a crucial component in the development and implementation of quality-based curricula. This study explores the effectiveness of various evaluation methods, including formative, summative, and authentic assessments, in measuring curriculum success. The results indicate that formative assessment positively contributes to students' understanding, while summative assessments often fail to accurately reflect students' abilities. Authentic assessments have proven to enhance student motivation and preparedness for real-world challenges. Student involvement in the evaluation process, the use of evaluation data for continuous improvement, and teacher training in diverse evaluation methods are key factors in enhancing evaluation effectiveness. This research emphasizes the importance of selecting appropriate evaluation methods aligned with curriculum objectives to achieve optimal educational outcomes. Thus, the findings provide valuable insights for curriculum development and evaluation practices in educational institutions.